Technological pedagogical content knowledge of Islamic education teachers in Kangar district primary school - Ramli, Muhamad Syazwan; a/l Rathakrishnan, Mohan; Mohd Nor, Nur Amanina (Academica Press Solutions, 2022)
The most crucial goal in line with how the digital world is changing is the seventh shift for Malaysian Education Development Plan which designed for use of ICT to improve learning quality. Teachers as the main driving force of this phase need to emphasize technological knowledge in parallel with pedagogical skills as well as mastery of content in professionalism. Thus, the Framework of Technological Pedagogical Content Knowledge (TPACK) is the main idea which able to guide the teacher to ensure the carrying of these elements in the teaching is successfully applied well. In this context, differences in knowledge of technology, pedagogy and content based on gender indicate the influence of demographic background in determining the degree of mastery of this TPACK framework. The study was conducted using descriptive and inference design. The research tool is a questionnaire distributed using a Google form. The questionnaire is constructed using a likert scale of 5. The data is analyzed using SPSS 27.0 to see the frequency, percent, and mean values. A sample of 30 Islamic Education teachers in Kangar district. The findings showed a high interpreting value of the level of technological pedagogical and content knowledge for Islamic Education teachers with an average mean 3.70 and 0.70 for the standard deviation. Moreover, by content with average degree for technical pedagogical competence among Islamic Education instructors varied significantly depending on the teachers' gender showing result of 1.011 based on the independent sample t-test. The significant difference in TPACK knowledge levels shows the difference level between male and female Islamic Education teachers in Kangar district primary schools.